PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Yosalia Noveda; Zelhendri Zen (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2022)
This research started from the phenomenon at school that the lack of student mastery of the subject matter of Islamic Religious Education, resulting in low student learning outcomes. This study aims to examine the use of the Make A Match learning model in Islamic Religious Education learning which can support the learning process because it can increase student activity in learning so that it can improve student learning outcomes. This study uses a quantitative approach with the type of Quasy Experiment. The population of this research is the students of class VII totaling 161 people consisting of 5 classes. The sampling technique was purposive sampling, namely class VII-2 and VII-5, each of which amounted to 33 people. The data collection technique used a test, in the form of an objective question of 40 items, and the data collection tool was a test sheet. The data was processed by difference test (t-test). From the results of the study, the average score of students who used the Make A Match learning model in class VII-5 was 80.30 higher than the control group in class VII-2 who did not use the model. Make A Match learning which the average learning outcome is 75.69. By using the t-test, the t-count is 4.09, while the t-table for the 0.05 level of significance is obtained by the t-table value of 1.6686. Thus tcount > ttable, which is 4.09 > 1.66. The results showed that there was a significant difference from the average value of the two classes. Thus, it can be concluded that the application of the Make A Match learning model has a high effect on student learning outcomes on the subject of Welcome to the Prophet Muhammad SAW My Beloved in the subject of Islamic Religious Education in class VII-5 SMP Negeri 3 Padang.Keywords : Make A Match, Learning Outcomes, Islamic Religious Education